MECHANISMS IN ENDOCRINOLOGY: Endogenous subclinical hypercortisolism and bone: a clinical review. Issue 6 (December 2016) - Chiodini, I; Vainicher, C Eller; Morelli, V; Palmieri, S; Cairoli, E; Salcuni, A S; Copetti, M; Scillitani, A
Abstract : In recent years, the condition of subclinical hypercortisolism (SH) has become a topic of growing interest. This is due to the fact that SH prevalence is not negligible (0.8–2% in the general population) and that, although asymptomatic, this subtle cortisol excess is not harmless, being associated with an increased risk of complications, in particular of osteoporosis and fragility fractures. As specific symptoms of hypercortisolism are absent in SH, the SH diagnosis relies only on biochemical tests and it is a challenge for physicians. As a consequence, even the indications for the evaluation of bone involvement in SH patients are debatable and guidelines are not available. Finally, the relative importance of bone density, bone quality and glucocorticoid sensitivity in SH is a recent field of research. On the other hand, SH prevalence seems to be increased in osteoporotic patients, in whom a vertebral fracture may be the presenting symptom of an otherwise asymptomatic cortisol excess. Therefore, the issue of who and how to screen for SH among the osteoporotic patients is widely debated. The present review will summarize the available data regarding the bone turnover, bone mineral density, bone quality and risk of fracture in patients with endogenous SH. In addition, the role of the individual glucocorticoid sensitivity in SH-related bone damage and the problem of diagnosing and managing the bone consequences of SH will be reviewed. Finally, the issue of suspecting and screening for SH patients with apparent primary osteoporosis will be addressed.